Teaching parallel and distributed computing concepts in simulation with WRENCH - Casanova, Henri; Tanaka, Ryan; Koch, William; Ferreira da Silva, Rafael (Journal of parallel and distributed computing, 2021)
Teaching parallel and distributed computing topics in a hands-on manner is challenging, especially at introductory, undergraduate levels. Participation challenges arise due to the need to provide students with an appropriate compute platform, which is not always possible. Even if a platform is provided to students, not all relevant learning objectives can be achieved via hands-on learning on a single platform. In particular, it is typically not feasible to provide students with platform configurations representative of emerging and future cyberinfrastructure scenarios (e.g., highly distributed, heterogeneous platforms with large numbers of high-end compute nodes). To address these challenges, we have developed a set of pedagogic modules that can be integrated piecemeal into university courses. These modules include simulation-driven activities for students to experience relevant application and platform scenarios hands-on. These activities are supported by simulators developed using the WRENCH simulation framework. After motivating and describing our approach, we present and analyze results obtained from evaluations performed in two consecutive offerings of an undergraduate university course. •Teaching Parallel and Distributed Computing (PDC) hands-on is challenging.•Simulation can be used for achieving hands-on teaching of PDC learning objectives.•Evaluation results show the effectiveness of simulation-driven PDC education.